Présence et influence assyriennes dans le royaume de Hamat - Baaklini, Adonice-Ackad, (Archaeopress Archaeology, 2021)
This volume assesses the importance and nature of the Assyrian presence in the kingdom of Hamat (northwest Syria) to determine whether there is a link between Assyrian control and the impact it exerted on the territories with which it came into contact.